Numerical simulation of flow field in complete condensing spinning: effects of suction unit and guiding device. Issue 7 (2nd July 2016) - Su, Xuzhong; Gao, Weidong; Liu, Xinjin
Abstract : Complete condensing spinning (CCS) is one kind of pneumatic compact spinning. A kind of hollow roller with strip groove structure on the surface is used to condense the fiber bundle and improve the yarn qualities. In this paper, the numerical simulation of flow field in CCS is studied using fluent software. Using AutoCAD Software, according to the physical parameters of the practical system, a three-dimensional (3D) model of the condensing zone is established firstly. Then, the numerical simulations of the flow field in CCS were presented. Three kinds of suction units, straight-type, long-skewed, and short-skewed, and three kinds of guiding devices, A-type, B-type, and C-type, were discussed. Corresponding simulations in the front, middle, and back condensing zone and arc line along the front roller surface direction were given and analyzed comparatively. It is shown that the flow field distribution in CCS is stable and can condense the fibers well. The shape of suction unit may mainly influence the output of fiber strand in the condensing zone and affect the yarn evenness. When compared with the long-skewed and short-skewed suction units, the straight-type suction unit is beneficial for the fiber strand output leading to better yarn evenness possibly. However, the distribution ranges of flow field in CCS with both long-skewed and short-skewed suction units are larger than that of the straight-type suction unit. Furthermore, comparing with that of without a guiding device, the direct transverse air condensing force in CCS using a guiding device is greatly larger, which is beneficial for reducing the yarn hairiness. However, the assisted condensing forces are smaller and make the yarn evenness possibly worse. Finally, the obtained numerical results are illustrated by spinning experiments.